Psychometric Properties of the LPC Scale: An Extension of Rice's Review - Schriesheim, Chester A.; Bannister, Brendan D.; Money, William H. (Academy of Management Review, 1979)
Chester A. Schriesheim, Brendan D. Bannister, William H. Money, Psychometric Properties of the LPC Scale: An Extension of Rice's Review, The Academy of Management Review, Vol. 4, No. 2 (Apr., 1979), pp. 287-290